Pengaruh Modal Sosial dan Kelembagaan terhadap Kinerja Usaha Tani Kapulaga di Lahan Perhutani Kabupaten Banyumas - Yuli Fatiah; Irene Kartika Wijayanti; Dindy Darmawati Putri (AGRITEXTS: Journal of Agricultural Extension, 2022)
Central Java is the second largest cardamom-producing province in Indonesia, with a total cardamom production of 9,814.4 kg in 2020. However, cardamom cultivation by farmers is less effective and is left without processing after harvesting. Such conditions cause cardamom yields to be not optimal in terms of quality and quantity. Institutions that run well are also predicted to be able to improve farm performance. The purpose of this research is to find out: (1) the characteristics of social and institutional capital of cardamom farmers in the perhutani land in Banyumas Regency; (2) the direct influence of social and institutional capital on the performance of cardamom farmers' farming in perhutani lands in Banyumas Regency; and (3) knowing whether the institutional variable is a moderating variable in the direct relationship between social capital and the performance of cardamom farming in perhutani land, Banyumas Regency. Data analysis was carried out by calculating productivity, profit, and feasibility to estimate the performance of cardamom farming in the forest area of Banyumas Regency. To determine whether social and institutional capital affects the performance of cardamom farming in perhutani land, Banyumas Regency, measured using Structural equation modeling (SEM) analysis. The results showed that the characteristics of social and institutional capital in the research location, on average, had a high category. Cardamom farming has been profitable and feasible to be developed. SEM-PLS analysis shows that the most dominant indicator measuring social capital is trust, while the most prevalent indicator measuring institutional is cultural values. Furthermore, social and institutional capital directly affect the performance of cardamom farming, but institutions cannot be a moderating variable of the social capital variable on farming performance.